(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
As a result of research into the production and economic activities of the farm, it was concluded that vacuum units with rotary vane vacuum pumps are used in milking units. The main disadvantage of rotary vane pumps is a significant oil consumption (up to 1 g/m³) and pollution of the environment with waste oil vapors. Silencers of most existing vacuum units do not allow separating waste oil from air and pollute the environment. A substantiated scheme, a developed design and a manufactured prototype of a silencer of an improved vacuum unit make it possible to reduce oil consumption by up to 95%.